2018
DOI: 10.3390/ijms19072019
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Inhibition of DNA Methylation Combined with Task-Specific Training on Chronic Stroke Recovery

Abstract: To develop new rehabilitation therapies for chronic stroke, this study examined the effectiveness of task-specific training (TST) and TST combined with DNA methyltransferase inhibitor in chronic stroke recovery. Eight weeks after photothrombotic stroke, 5-Aza-2′-deoxycytidine (5-Aza-dC) infusion was done on the contralesional cortex for four weeks, with and without TST. Functional recovery was assessed using the staircase test, the cylinder test, and the modified neurological severity score (mNSS). Axonal plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 56 publications
(97 reference statements)
0
23
0
Order By: Relevance
“…The primary purpose of this study was to understand the differences in gene expression that occur over time after stroke. Based on previous studies demonstrating time-specific differences after injury in the rat photothrombosis model [23], we distinguished systematically the brain after stroke at the acute (1 week post-injury), subacute (4 weeks post-injury), and chronic (8 weeks post-injury) phases. The advantage of the photothrombosis model is the ability to generate an injury with a similar size within distinct functional areas of the cortex; thus, this model is suitable for assessing the overall pattern of genetic alterations that occur after stroke [24,25].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The primary purpose of this study was to understand the differences in gene expression that occur over time after stroke. Based on previous studies demonstrating time-specific differences after injury in the rat photothrombosis model [23], we distinguished systematically the brain after stroke at the acute (1 week post-injury), subacute (4 weeks post-injury), and chronic (8 weeks post-injury) phases. The advantage of the photothrombosis model is the ability to generate an injury with a similar size within distinct functional areas of the cortex; thus, this model is suitable for assessing the overall pattern of genetic alterations that occur after stroke [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…The intact areas of ipsilateral and contralateral hemispheres were measured using ImageJ software, then the volume of intact hemisphere was calculated (intact area: × 0.04 × 20) and summed among the slices. The total infarction volume was determined: the volume of contralateral hemisphere in comparison to the volume of intact area in the ipsilateral hemisphere [23,38].…”
Section: Determination Of the Infarction Volumementioning
confidence: 99%
See 2 more Smart Citations
“…In particular, increased DNA methylation within the CpG island overlapping with the promoter of ELOVL2 was tightly correlated with the age of the individual 33 . We attempted to demethylate this region using 5-Aza-dc, known to inhibit the function of DNMTs also in nondividing neurons [23][24][25] . We reported that upon intravitreal injection of the compound, the DNA methylation is reduced, gene expression is upregulated, and visual function is maintained in the treated eye compared with the contralateral control.…”
Section: Methylation Of the Regulatory Region As A Mechanism Of Age-dmentioning
confidence: 99%